Pengaruh Kompensasi Terhadap Kinerja Karyawan Melalui Komitmen Organisasi Sebagai Variabel Mediasi (Study Pada Mitra Driver Go-Jek Di Surakarta) - praptiestrini . (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2018)
The problem of this study is that the factor of compensation and decreasing employee commitment has an impact on declining employee performance, especially income of Gojek drivers. This research aims to analyses (1) significance effect of compensation on organizational commitment (2) significance effect of compensation on employee performance (3) significance effect of organizational commitment on employee performance (4) the effect of compensation on employee performance, through organizational commitment as the mediating variable. This research using samples of 100 drivers Go-jek in Surakarta city with accidental sampling technique. Data collecting with questionnaire technique through validity and reliability test. To test the hypothesis using path analysis. Findings (1) compensation has significance effect on organizational commitment. (2) compensation has significance effect on employee performance. (3) organizational commitment has significance effect on employee performance. (4) organizational commitment mediates of the effect compensation on employee performance. Contribution of this research can be used as policy of Gojek company to pay more attention of increasing compensation which can increase commitment and employee performance. This research can contribute to the development of human resource literature and as a reference for similar research.